(3ajV GdbOjQ TQM GdLGeY GdUZjQs - (3GdMOGOj GdbGgQj GdefGhj, Rjf GdOjf, eMeO YHO GdQADa Hf JGL GdYGQajf Hf Ydj Hf Rjf GdYGHOjf, J (B1031 (3g`s ((3GdLGeY GdCehjs)
(3ChdgG (B:s
(3HYO GdHSedI ; HGH GdgeRI dGe (B((3CdHGf GdHbQ TaGA(B) (3ef GdCeQGV GdShOGhjI hGdZe hGdhShGS hjMaX GdUMI hjQWH GdHOf hjWdb GdHOf HGYJOGds
(3BNQgG (B:s
(3Yf YcQeI GdHQjOj CMO GdCYdGe ehdi GHf YHGS eJcde aj YbjOJg hbjd jcPH Ydi SjOg (B( (3eQSdG (B) (3bGd GdMGaX GdYQGbj hdCMeO ef MOjK YGFTI HSfO MSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3eYLe GdeDdajf (B2 / 143s
(3cTa GdXfhf (B1 / 561s
(3GdHOQ GdWGdY (B1/ 357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs